Pemberdayaan Kelompok Tani Hutan di Desa Girimulyo Melalui Pelatihan Pembuatan Pupuk Organik Cair: Empowerment of Forest Farmer Groups in Girimulyo Village Through Training on Liquid Organic Fertilizer Production - Nufus, Malihatun; Al Insan, Raden Muhammad Hakim; Al Hadi, Ihsan; Dewi, Vadhila Arista; Sefriyani, Veni Elisa; Pratama, Winadhy Surya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Implementation of sustainable agriculture promotes environmental sustainability. These start with the farmer using organic-based fertilizer. Therefore, this community service activity aimed to improve the farmers' knowledge and skills to produce liquid organic fertilizer (LOF) as an alternative to chemical fertilizer to support sustainable agriculture. The target of this activity is four Forest Farmer Groups (FFG) in Girimulyo Village, Jatipurno, Wonogiri. The methods used are lectures, discussions, and direct practice. Based on the initial survey, only 10% participants understood the basic concept of LOF. Therefore, the presentation covered the definition, benefits, and process of making LOF and the negative impacts of excessive use of chemical fertilizers. The activity continued with a hands-on practice of making LOF using readily available media such as dry leaf litter, livestock manure, and adding EM4 starter and molasses. A total of 30 participants followed the activity attentively, and discussions took place during the material explanation and the hands-on practice. The evaluation results showed an increase in the participants' understanding and skills. This activity is expected to encourage farmer independence in LOF production and open up sustainable business opportunities in the organic farming sector.